Textual Orality in Pesantren Tafsir: Reimagining Mangaji Tudang Through Tafsir Surah ʿAmma by AGH. As’ad Al-Bugisy - Muhammad Alwi HS; Muharrahman Muharrahman; Muhsin Mahfudz; Hamzah Harun; Muhammad Yusuf; Witry Octasari Aritonang; Daffa Rizqi Prayudya (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2026)
This article examines the relationship between oral and written traditions in the corpus of pesantren Qur’anic tafsir through Tafsir Surah ʿAmma bil-Lughah al-Bugisiyyah by AGH. As’ad Al-Bugisy, a work that emerged from the mangaji tudang tradition of the As’adiyah Pesantren in South Sulawesi. Although studies of pesantren tafsir have extensively explored philological, linguistic, ideological, and social dimensions, the dimension of orality within tafsir texts as a representation of pesantren teaching traditions has received limited systematic attention in tafsir scholarship. This study aims to reveal how the practice of mangaji tudang is represented in the tafsir text through the concept of textual orality and how the tradition has been transmitted and transformed after AGH. As’ad. This study employs a qualitative textual approach, using Tafsir Surah ʿAmma as its primary corpus. The analysis is supported by field observation, digital documentation of contemporary Mangaji Tudang practices at the As'adiyah Pesantren, as well as relevant scholarly literature and historical sources. The findings demonstrate that orality in the tafsir is manifested through three principal forms: a presentation structure that follows the rhythm of religious instruction, pedagogical strategies that reflect pesantren teaching practices, and the use of terms and experiences closely connected to the everyday life of Bugis society. The study further finds that the tafsir functions as a record of mangaji tudang, preserving not only AGH. As’ad’s pedagogical experience but also serving as a medium for the transmission and transformation of Islam based on Ahl al-Sunnah wa al-Jamāʿah (ASWAJA) within Bugis culture. These findings advance pesantren tafsir studies by establishing textual orality as an analytical framework for non-Javanese exegetical traditions, and by demonstrating that local Qur’anic commentaries function as living archives in which pedagogical practice, cultural memory, and Islamic knowledge transmission are simultaneously encoded and sustained.